THE CONSERVATION AND RECUPERATION OF HISTORICAL EDUCATIONAL HERITAGE FROM INSTITUTIONALIST AND PEDAGOGICAL PERSPECTIVES: THE RESTORATION OF THE CHAIR OF LATIN STUDIES OF LOIS VILLAGE (LEÓN, SPAIN) - Poy Castro, Raquel; Juan Fernández, Jorge de (Historia y Memoria de la Educación, 2024)
The purpose of this research focuses on analyzing the process followed in the recovery of the educational historical heritage based in the case study of the Lois Chair of Latinity, founded on the Leon mountains in 1744, and which remained active for more than two centuries. This foundation was an extraordinary educational and social experience deserving of its conservation and recovery. The restorative process has been studied from a triple perspective including the normative, institutional and social context. The historical method has been used following the conventional phases in which, firstly, a selection of the sources is made. The primary sources include the oral ones, embodied in the in-depth interviews carried out with the agents involved in the phenomenon studied, as well as the written ones from original documents of the Diocesan Archive of León. After collecting the information, an exhaustive critical analysis was carried out, concluding that the conservation of the Lois Chair has been possible thanks to the strong feeling of the local community acting as the promoter of the project and also with the help of the institutions involved (bishopric, city council and regional administration) which have led the efforts in architectural conservation. It’s remarkable that it would be helpful for the recovery of the educational historical heritage, in addition to the architectural action, to include the pedagogical and educational values in the planning process.